Meningkatkan Keterampilan Motorik Halus Melalui Kegiatan Menggunting Pada Kelompok A di Tk St. Theresia I Pangkalpinang Bangka - Imelda Indah Bulan (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Classroom action research is based on the low Fine Motor Skills of children, so the implementation of this study aims to improve children's fine motor skills through pattern cutting activities in group A at St. Theresia I Pangkalpinang Kindergarten. The method used in this research is classroom action research which is carried out as an effort to overcome problems that arise in the classroom. This method is carried out with three stages, namely planning, implementation, and reflection. The research subjects were group A students of St. Theresia 1 Pangkalpinang Bangka Belitung Kindergarten, totaling 22 children. The object of this research is fine motor skills. The data collection method used was observation. Technical data analysis is done descriptively qualitative. The success indicator set is at least 85% of 22 children reach the category of developing as expected. This research was conducted in two cycles. The results showed that cutting activities can improve the fine motor skills of 22 children in group A of St. Theresia I Pangkalpinang Kindergarten. The improvement can be seen from the observation of learning outcomes where there was an increase in the category of developing as expected (BSH) from originally only 3 children (as much as 14%) at the beginning of Cycle I increased to 19 children or 86% at the end of Cycle II. Based on the minimum success indicator set at 85%, this shows success in improving fine motor skills through cutting activities in group A at St. Theresia I Pangkalpinang Kindergarten.Keywords: fine motor skills, cutting activities, early childhood